Overexpression of the GmERF071 gene confers resistance to soybean cyst nematode in soybean - Erhui Xiong; Jiaqi Xu; Pingzhang Feng; Yun Lian; Xiaoling Zhi; Ke Li; Erhan Zhang; Bing Li; Shijie Zhao; Changzhong Liu; Chengyu Wei; Panpan Li; et al. (The Plant Genome)
Abstract Soybean cyst nematode (SCN) is one of the most harmful pests, causing major reductions in soybean yield globally. The validation and functional characterization of SCN resistance genes are crucial to improving soybean yield worldwide. Herein, we describe an SCN resistance gene, GmERF071 (Glyma.19g262700). GmERF071 is a hydrophilic, unstable protein with an AP2/ERF subfamily ethylene response transcription factor domain, which is localized in the nucleus. Overexpression of GmERF071 enhanced SCN resistance in the soybean stable genetic transformation and root systems. RNA‐seq analysis revealed 394 upregulated and 132 downregulated differentially expressed genes (DEGs) in GmERF071 overexpression transgenic plants. The DEGs participated in plant‐pathogen interactions, mitogen‐activated protein kinase signaling, plant hormone signal transduction, response to chitin, response to carbohydrates, response to wounding in starch and sucrose metabolism, phenylpropionic acid biosynthesis, and flavonoid biosynthesis. Nine candidate DEGs were verified using real‐time quantitative reverse transcription PCR. These results suggest that GmERF071 plays a key role in SCN resistance and could be used in genomics‐assisted breeding to develop soybean varieties with increased resistance to SCN.